Where did all the Fascists go? - Nylander,Bo (2010)
The Fascist movement in Sweden is a field that hasn’t attracted a great deal of research. This paper attempts to create a working theory as to why the Swedish Fascist movement is marginalized in the municipality of Lund while the Fascist presence is strong in the neighboring city of Helsingborg using qualitative methods. This paper proposes four factors for understanding this difference: the material/societal factor, the absence of an autonomous left movement, the leadership factor and the resource factor. These factors are applied to the case of Lund/Helsingborg in order to determine if there is indeed a relationship. The comparison shows that the factors are all present in Helsingborg while they are absent in Lund.
Keywords: Lund; Fascism; extremism; Helsingborg; Sweden